Nexie ebook - Cawthon, Scott (Five Nights at Freddy's: Tales from the Pizzaplex, 2023)
Five Nights at Freddy's fans won't want to miss this collection of three chilling stories that will haunt even the bravest player... Can you keep a secret? . . . Astrid doesn't tell anyone about the strange things her Buddytronic doll has been up to. Kara convinces a Pizzaplex employee no one will know if he lets her spend a little more time in the VR attraction. And a Fazbear Entertainment engineer's custom project has surprises in store for anyone who encounters it. But in the world of Five Nights at Freddy's, secrets never stay hidden for long . . . In this sixth volume, Five Nights at Freddy's creator Scott Cawthon spins three sinister novella-length tales from uncharted corners of his series' canon. In the world of Five Nights at Freddy's, everything comes with a price to pay. Readers beware: This collection of terrifying tales is enough to rattle even the most hardened Five Nights at Freddy's fans.